2011
DOI: 10.1007/s00109-011-0761-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of renin-angiotensin system (RAS) reduces ventricular tachycardia risk by altering connexin43

Abstract: Renin-angiotensin system (RAS) activation is associated with arrhythmias. We investigated the effects of RAS inhibition in cardiac-specific angiotensin-converting enzyme (ACE) overexpression (ACE 8/8) mice, which exhibit proclivity to ventricular tachycardia (VT) and sudden death because of reduced connexin43 (Cx43). ACE 8/8 mice were treated with an ACE inhibitor (captopril) or an angiotensin receptor type-1 blocker (losartan). Subsequently, electrophysiological studies were performed, and the hearts were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Hearts were rapidly removed at either 48 h or 5 day postcoronary occlusion, and the left ventricle was dissected free and placed in warm oxygenated saline, epicardial side up. Dye spread was done as described previously (13,24). With a 26-gauge needle a pinhole was made and 2.5% Lucifer Yellow in 150 mM lithium chloride was pipetted onto the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Hearts were rapidly removed at either 48 h or 5 day postcoronary occlusion, and the left ventricle was dissected free and placed in warm oxygenated saline, epicardial side up. Dye spread was done as described previously (13,24). With a 26-gauge needle a pinhole was made and 2.5% Lucifer Yellow in 150 mM lithium chloride was pipetted onto the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged stimulation of cardiomyocytes with isoprenaline increases Cx43 expression through activation of Erk1/2 (Salameh et al, 2013;Salameh et al, 2009); however, in co-cultures of cardiomyocytes and fibroblasts, paracrine factors released by fibroblasts suppress the isoprenaline-induced increase in Cx43 expression in cardiomyocytes (Pedrotty et al, 2009;Salameh et al, 2013). Such suppression can partially be reversed by blocking angiotensin II or PKC (Pedrotty et al, 2009), and in cardiac tissue from mice, inhibition of the renin angiotensin system increases Cx43 expression (Iravanian et al, 2011). …”
Section: Regulation Of Cx43 In Heart and Cnsmentioning
confidence: 99%
“…The activation of cSrc leads to Cx43 downregulation, impaired gap junction function, slowed cardiac conduction and increased incidence of ventricular arrhythmias and SCD. 35, 257 The downregulation of Cx43 and increased risk for arrhythmias in ACE8/8 mice are alleviated by pharmacologic inhibition of RAS 258 and cSrc. 257 It has been shown that increased myocardial p-cSrc leads to Cx43 reduction through the competition between p-cSrc and Cx43 for the binding with zonula occludens-1, a scaffolding protein at the intercalated disk, resulting in Cx43 destabilization and degradation.…”
Section: Mechanisms Linking Increased Cardiac Oxidative Stress To Venmentioning
confidence: 99%